Customer Behavior in the Processed Wood Industry during Post Covid-19 Pandemic - Afifatus Solehah, Artika; Eddyono, Fauziah (PT Mattawang Mediatama Solution, 2025)
As the trend of home renovations increases during the Covid-19 pandemic, a global demand for wood products has declined significantly, mainly due to rising prices. This situation poses a major challenge for wood processing companies, such as PT. Tanahmas Kencana Abadi, which are maintaining its competitive advantage in the middle of increasingly fierce competition and declining consumer purchasing power. Therefore, evaluating customer satisfaction and loyalty is crucial. This study analyzes the factors that influence customer satisfaction and loyalty, focusing on product quality and price. The study population consisted of 50 B2B plywood companies, both domestic and international, selected using a saturated sampling technique. The data collected were analyzed through Smart-PLS, using a Structural Equation Modeling approach focusing on path coefficients and t-tests. The study findings reveal that the environmentally friendly aspect is the most influential factor in the correlation between product quality and customer satisfaction. In addition, customer satisfaction affects customer loyalty and moderates the correlation between product quality and loyalty. In contrast, price does not significantly affect customer satisfaction or loyalty. Based on these findings, companies are advised to improve the certification and marketing communications related to environmentally friendly products to strengthen and enhance their competitive advantage.